Fenomenologis Pinjaman Online di Kalangan Mahasiswa Santri Pondok Pesantren Al Falah Mojokerto, Jawa Timur - Ahmad Jainuri; Lucky Nugroho; Yosi Mardoni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The aim of this research is to find out how many santri students have online loans, the purpose of santri students making online loans and find out how santri students pay off these online loans. This research method uses a descriptive qualitative method by conducting surveys and in-depth interviews with Islamic boarding school students who have online loans. Furthermore, the descriptive qualitative method aims to answer the problem formulation in this research. The results of this research are (i) the majority of santri students have online loan facilities, (ii) all santri students use online loans for consumptive purposes, (iii) the source of installment payments for online loan payments comes from the santri students' pocket money. The implication of this research is to provide information and references to stakeholders regarding the reach of online loans which have spread among Islamic boarding schools. The novelty of this research is related to the research object, namely online loans among Islamic boarding schools.